Long‐term follow‐up of ribavirin‐free DAA‐based treatment in HCV recurrence after orthotopic liver transplantation. (31st January 2018) - Beinhardt, Sandra; Al‐Zoairy, Ramona; Kozbial, Karin; Stättermayer, Albert F.; Maieron, Andreas; Stauber, Rudolf; Strasser, Michael; Zoller, Heinz; Graziadei, Ivo; Rasoul‐Rockenschaub, Susanne; Trauner, Michael; Ferenci, Peter; et al.
Abstract: Background & Aims: Excellent efficacy and safety profile of second‐generation DAA combinations improved treatment of chronic hepatitis C (HCV) as well as in HCV recurrence after orthotopic liver transplantation (OLT). The need of ribavirin addition is under debate as anaemia and decreased renal function are prevalent in transplant cohorts. The aim of this study was thus to assess safety and long‐term efficacy of RBV‐free DAA combinations in HCV‐recurrent patients after OLT. Patients & Methods: A total of 62 OLT recipients (male: 50%/81%; age: 60.7 ± 8.5 years [mean ± SD]; GT ‐ 1: 48, GT ‐ 3: 9, GT ‐ 4: 5; cirrhosis: 34%/55% [7%/21% decompensated], fibrosing cholestatic hepatitis: 1%/2%) received RBV‐free treatment with second‐generation DAA combinations: sofosbuvir (SOF)/daclatasvir (DCV): 42%/68%, SOF/simeprevir (SMV): 10%/16%, SOF/ledipasvir (LDV): 6%/10% and PrOD: 4%/7%. Results: Data of at least 96 weeks of FUP after treatment cessation (mean: 120; up to 167 weeks) were analysed. All patients showed on‐treatment response. By intention‐to‐treat (ITT) analysis, SVR12 was 97% (60/62, GT‐1a: 11/11 [100%]; 1b: 33/34 [97%]; 1g: 1/1 [100%]; subtype not specified: 2/2 [100%]; GT3a: 9/9 [100%]; GT4: 4/5 [80%]) compared to SVR96 of 89% (55/62). No late relapses occurred. In total, 16 severe adverse events occurred, including two newly diagnosed carcinoma (lung cancer, hepatocellular carcinoma). Six patients died; one at treatment week 24 (HCV‐RNA undetectable) and five during treatment‐free FUP and after achieving SVR (SVR4: N = 1, SVR12: N = 3, after SVR96: N = 1 respectively). Reasons for death were: multi‐organ failure (N = 4), impaired graft function (N = 1) and unknown (N = 1). Conclusion: RBV‐free DAA combinations for the treatment of HCV recurrence after OLT are highly efficacious and well tolerated. Our long‐term data show that viral eradication is durable but not necessarily translated into beneficial long‐term clinical outcome.